BEING BILINGUAL IN EARLY AGES: IS IT ADVANTAGEOUS? - Kalisa, Pasca (Language Circle: Journal of Language and Literature, 2014)
Age as a factor to succeed in childrenâs second language acquisition (SLA) has been a controversial issue for over a period of time. Some studies analyzing the issue found that age is the main factor to determine childrenâs success in SLA. Responding to the issue, this paper aims at exploring the notion of early bilingualim compared to monolingual children. In addition, this paper mainly focuses on the advantages of being bilingual in a earlier ages. The discussion reveals that bilingual children get more benefits in their language performance than monolingual children. As conclusion, it is suggested that âadditive bilingualismâ could be applied in Indonesia which English as the foreign language is used at school, while using Indonesian is still maintained at home.